Roots of Zoroastrianism in Iran and India - Samavati, Fatemeh (Brill | Manohar Publishers & Distributors, 2023)
Thirteen centuries have passed since Zoroastrian Iranians first landed in India and began their life anew. In their adopted homeland, they proved to be the true bearers of the name and fame of their illustrious ancestors. Pages of history are still alive with the noble deeds of ancient Iranians and their descendants, reflecting their past glory in the mirror of their small community. Their Zoroastrian virtues have made modern Parsis proud. The community has secured a respectable place in the social, intellectual, and economic life of the teeming millions of India. They have amassed vast fortunes and have given away equally vast sums for philanthropic purposes without distinguishing between caste, colour, or creed. This book, goes deep into the early history of Zoroastrianism in Iran and moves on to analyze the chequered history of long-standing Iranian and Zoroastrian connections, as well as cultural norms associated with Parsis in India, for close to a millennium, c. 700-1700 CE.